From the imperfect peace to the pacifist agency - Jiménez Arenas, Juan Manuel (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of the study is to contribute from the dual perspective of imperfect peace and epistemological turn to review in a critical way the concept of power as the basis for pacifist agency. Originality this work focuses, for the first time, on agency as a possibility for peace to take part in more personal, public and political spaces. Method is a qualitative research work that starts, from a complex perspective, from the concept of imperfect peace and the epistemological turn, using the strategies of critical analysis of research texts for peace and writings that deal with the concept of power, especially of Hannah Arendt, Michael Foucault, Michael Mann, Kenneth Boulding and John Holloway, among others. Their dialogue allows us to conclude that power can also be considered as the ability that all human beings have to act in a coordinated way in order to promote the development of desirable human skills. Understood in this way, power generates peace, which must occupy the greatest personal, public and political space. Thus, this extension of peace should not be valued only as a measure of pacifist empowerment, but also as a consequence of the peacemaker agency.